2018
DOI: 10.1007/s00384-018-3089-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gender on early colonic anastomotic wound healing

Abstract: Our findings point towards a less favorable collagen metabolism in colonic anastomoses of male compared with female rats during early wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
1
16
1
Order By: Relevance
“…TGF- β is closely involved in collagen metabolism during early colonic anastomotic wound healing [ 31 , 32 ]. We have previously shown a correlation between TGF- β 1 and soluble collagen indicative of collagen synthesis in anastomotic healing on day 3 [ 19 ]. TGF- β 1 levels were reduced with ZP1849 treatment on day 5, an observation also reported by Redstone et al [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TGF- β is closely involved in collagen metabolism during early colonic anastomotic wound healing [ 31 , 32 ]. We have previously shown a correlation between TGF- β 1 and soluble collagen indicative of collagen synthesis in anastomotic healing on day 3 [ 19 ]. TGF- β 1 levels were reduced with ZP1849 treatment on day 5, an observation also reported by Redstone et al [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The noninjured colon segment was snap-frozen in liquid nitrogen and stored at -80°C until analysed for mRNAs. An end-to-end single-layer anastomosis was made using 8 interrupted, inverted polypropylene monofilament 6/0 sutures (Prolene®) placed 2 mm from the resection margins [ 18 , 19 ]. Saline (37°C) was applied to the abdominal cavity (5 mL) and subcutaneous tissue (2.5 mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Recent research provides novel evidence that visceral adipose tissue of female mice possesses greater levels of pro-angiogenic factors and vascularity than males in response to a high fat diet, and collagen metabolism is impaired in the colonic anastomosis of male compared with female rats during early wound healing. 21,22 In gonadally intact rodents, it has been suggested that males should be compared to females on specific days of their 4 day estrous cycle to generate reliable data. 23 However, a meta-analysis comparison of male and female rodents, with no regard to the stage of the estrous cycle, established that variability in most traits was equivalent in females and males, and that for most end points, it was unnecessary to stage the estrous cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The NIH has recently recognized this gap in scientific knowledge and now mandates that studies be conducted in both sexes 1 . Recent research provides novel evidence that visceral adipose tissue of female mice possesses greater levels of pro‐angiogenic factors and vascularity than males in response to a high fat diet, and collagen metabolism is impaired in the colonic anastomosis of male compared with female rats during early wound healing 21,22 …”
Section: Discussionmentioning
confidence: 99%